Electrochemical impedance spectroscopy of La0.6Sr0.4Co0.2Fe0.8O3-δ nanofiber cathodes for intermediate temperature-solid oxide fuel cell applications: A case study for the 'depressed' or 'fractal' Gerischer element. (1st October 2019) - Costamagna, Paola; Sala, Elena Marzia; Zhang, Wenjing; Lund Traulsen, Marie; Holtappels, Peter
Abstract: Electrospun La0.6 Sr0.4 Co0.2 Fe0.8 O3-δ (LSCF) continuous unbroken nanofiber cathodes are investigated through electrochemical impedance spectroscopy, carried out on symmetrical button cells employing a Ce0.9 Gd0.1 O1.95 (CGO) electrolyte. The Nyquist plot of the EIS experimental data at 550 °C shows a single arc displaying typical 'normal' or 'pure' Gerischer shape. With increasing temperature (600–750 °C), this single arc gradually shrinks and deforms, showing a 'depressed' or 'fractal' Gerischer behavior. Finally, for temperatures higher than 750 °C, this arc further shrinks, becoming practically a depressed semicircle at 950 °C. These results demonstrate that the depressed Gerischer behavior, whose physical significance has never been demonstrated on theoretical grounds, is not an intrinsic feature of the electrode, since it appears in a clear manner only at certain well defined temperatures, while it disappears at other operating temperatures. Equivalent circuit model fitting is accomplished through the depressed Gerischer element, and also through an alternative circuit based on a pure Gerischer coupled in series to an RQ element. The superior fitting capability of the latter equivalent circuit is demonstrated. The latter circuit allows to assess separately the impedance contribution of the electrode bulk, associated to the pure Gerischer element, and of the electrode/electrolyte interface, associated to the RQ element, providing a powerful tool in view of understanding where the resistances are concentrated, which is the first step for an optimization of the electrode structure. In the LSCF electrospun cathodes investigated here, the higher resistance is associated to the bulk process, and it is proposed to be related to the high void degree (37.5%). Furthermore, with the latter circuit, the EC fitting parameters, having a physical meaning, provide information about the electrochemical process occurring along the LSCF nanofibers, and at the LSCF/CGO interface.